Genome editing for enhanced abiotic stress tolerance in selected cereal (Poaceae) crops: current applications, tools, and future perspectives - Amin-Asyraf Tamizi,; Rabiatul-Adawiah Zainal-Abidin,; Anis Afuza Md-Yusof,; Nurul Asyikin Mohd-Zim,; Mohd Syahmi Salleh,; Nur Sabrina Ahmad Azmi,; Zarina Zainuddin,; Sarahani Harun,; Rogayah Sekeli,; Nurul Hidayah Samsulrizal, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Recent progress in genome editing (GEd) technology offers an opportunity to accelerate the breeding of improved crops with enhanced resistance and high tolerance to drought and salinity. In this article, we highlight four programmable site-specific nucleases that are considered prominent GEd technologies: meganucleases, zinc-finger nucleases (ZFNs), transcription activator-like effector nucleases (TALENs), and clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR associated (Cas) nucleases. We then focus on the application of CRISPR/Cas9 system and access the transformation methods that have been used to deliver the system into major cereal crops including rice (Oryza sativa), maize (Zea mays), barley (Hordeum vulgare), sorghum (Sorghum bicolor), and wheat (Triticum aestivum). This review further emphasises the applications of the CRISPR/Cas9 system to impart tolerance to two major abiotic stresses, salinity and drought, in these selected crops. Finally, we summarise bioinformatics tools that are available for cereal genome editing works, including guide RNA (gRNA) design and post-editing analysis tools. This review provides an overview of current progress, identifies research gaps, and offers perspectives for prospective scientists embarking on genome editing in cereals and related crops.